Teachers' Perceptions About Oral Corrective Feedback and Their Practice in EFL Classrooms - Edith Hernández Méndez; María del Rosario Reyes Cruz (Universidad Nacional de Colombia, 2012)
Corrective feedback has been discussed mainly in second language acquisition contexts, but less has been done concerning corrective feedback in foreign language settings. In this descriptive study, conducted at a Mexican university, our aims were to identify the perceptions of instructors of English as a foreign language about corrective feedback and its actual practice in their classrooms. A semi-structured interview and a questionnaire were used to collect the data. The results show that teachers in general have a positive perception of oral corrective feedback. However, some consider it as optional because instructors are very concerned with students' feelings and emotions. Unfocused oral corrective feedback and implicit strategies are predominant in practice. Corrective feedback provided by the instructor is preferred to that provided by peers. Self-correction is the least popular.